Significant Reductions in Gag-Protease-Mediated HIV-1 Replication Capacity during the Course of the Epidemic in Japan - Nomura, Shigeru; Hosoya, Noriaki; Brumme, Zabrina L.; Brockman, Mark A.; Kikuchi, Tadashi; Koga, Michiko; Nakamura, Hitomi; Koibuchi, Tomohiko; Fujii, Takeshi; Carlson, Jonathan M.; Heckerman, David; Kawana-Tachikawa, Ai; et al. (Journal of Virology, 2012)
Human immunodeficiency virus type 1 (HIV-1) evolves rapidly in response to host immune selection pressures. As a result, the functional properties of HIV-1 isolates from earlier in the epidemic may differ from those of isolates from later stages. However, few studies have investigated alterations in viral replication capacity (RC) over the epidemic. In the present study, we compare Gag-Protease-associated RC between early and late isolates in Japan (1994 to 2009). HIV-1 subtype B sequences from 156 antiretroviral-naïve Japanese with chronic asymptomatic infection were used to construct a chimeric NL4-3 strain encoding plasma-derived gag-protease. Viral replication capacity was examined by infecting a long terminal repeat-driven green fluorescent protein-reporter T cell line. We observed a reduction in the RC of chimeric NL4-3 over the epidemic, which remained significant after adjusting for the CD4+ T cell count and plasma virus load. The same outcome was seen when limiting the analysis to a single large cluster of related sequences, indicating that our results are not due to shifts in the molecular epidemiology of the epidemic in Japan. Moreover, the change in RC was independent of genetic distance between patient-derived sequences and wild-type NL4-3, thus ruling out potential temporal bias due to genetic similarity between patient and historic viral backbone sequences. Collectively, these data indicate that Gag-Protease-associated HIV-1 replication capacity has decreased over the epidemic in Japan. Larger studies from multiple geographical regions will be required to confirm this phenomenon.